PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA MATERI KELANGSUNGAN HIDUP KELAS IX.C DI SMPN 18 PEKANBARU TAHUN 2017 - ASNIDAR, ASNIDAR (Komunitas Manajemen Kompetitif, 2018)
Abstract This study aims to determine the improvement of students' learning outcomes in the subjects of Sciences (IPA) on survival materials with the application of cooperative learning type STAD in class IX.C in SMP Negeri 18 Pekanbaru. This form of research is a classroom action research with as many as two rounds (Cycle). Each round is done with four stages of planning, implementation, observation and reflection. The subjects of this study are the students of class IX.C in SMP Negeri 18 Pekanbaru with a total of 38 students consisting of 19 male students and 19 female students. The data obtained in the form of science learning outcomes obtained from the test and observation sheet of teaching and learning activities. Data collection methods used include test, observation and documentation. From the results in the first cycle of student learning outcomes to 40% with inactive classification. While in the second cycle of students in learning results increased to 60% with a very active classification. This situation indicates that the improvement in the learning process of IPA with the application of cooperative learning type STAD in science subjects in class IX.C students at SMP Negeri 18 Pekanbaru can be said fully successful. Keywords: Science, Survival, STAD